2018
DOI: 10.1177/0272684x18821305
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Health Literacy in Kansas Using the Behavioral Risk Factor Surveillance System

Abstract: Health literacy continues to be an important research topic as part of population-based assessments for overall health issues. The objective of this continuation study was to examine the health literacy rates and health outcomes as measured by the Kansas Behavioral Risk Factor Surveillance System (BRFSS) survey. A cross-sectional research design was used. Health literacy data were extracted from the state-specific module of the BRFSS telephone survey. Demographic and health status variables were extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The analyses showed a significant association between all the categories of public support with having inadequate health literacy, except for voluntary early retirement pension. The results are consistent with our assumption and current body of evidence that the unemployed population has a higher likelihood of having inadequate health literacy [17][18][19][20][21][22]32]. However, it should be noticed, that the setting and the measures differ from the current study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The analyses showed a significant association between all the categories of public support with having inadequate health literacy, except for voluntary early retirement pension. The results are consistent with our assumption and current body of evidence that the unemployed population has a higher likelihood of having inadequate health literacy [17][18][19][20][21][22]32]. However, it should be noticed, that the setting and the measures differ from the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Therefor it is also relevant to investigate whether working and the individual's occupational situation influence the level of health literacy, impacting the ability to maintain and promote a healthy life [16]. The research-based knowledge on the association between employment status and health literacy is scarce but the evidence shows that different context-dependent status of employment are associated with health literacy [17][18][19][20][21][22]. Thus, this study aimed to identify whether the health literacy level differs dependent on the individuals' employment situation by comparing different population groups who are not employed with those who are employed.…”
Section: Introductionmentioning
confidence: 99%
“…All measures were collected via the KS BRFSS survey. 6 , 9 The survey is a statewide survey conducted by the state health department and supported by the Centers for Disease Control and Prevention (CDC). It is a randomized digit dialing telephone survey (including both landlines and cell phones) to collect self-reported information including health risk behaviors, clinical preventive health practices, and health care access that are associated with the leading causes of morbidity and mortality in the United States.…”
Section: Methodsmentioning
confidence: 99%
“… 8 , 9 A previous study demonstrated individuals with low levels of health literacy were 7 times as likely to be unsure of at least 1 health condition than those with high health literacy using the BRFSS survey tool as a measure of population health. 9 …”
Section: Introductionmentioning
confidence: 99%
“…The item set was developed first by reviewing existing brief HL self-reports and screening tools 17 as well as earlier state-specific HL item sets for the BRFSS. 18 Selected questions were subjected to cognitive testing to identify optimal wording and format. Each item could be scored from 0 ("very difficult") to 3 ("very easy").…”
Section: Methodsmentioning
confidence: 99%